Synthesis and characterization of simple cost-effective trans-A(2)BC porphyrins with various donor groups for dye-sensitized solar cells - Kumar, Ravi; Sankar, Muniappan; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (New Journal of Chemistry, 2016)
We have designed and synthesized a series of simple cost-effective 'push-pull' Zn(II) porphyrin dyes containing various electron donors such as 2-thienyl, pyrenyl, phenyl, 4'-bromophenyl, 4'-tbutylphenyl and 4'-carboxyphenyl acceptor moieties in three steps. Their optical absorption spectra, electrochemical redox and photovoltaic properties have been investigated in detail. The overall power conversion efficiencies (Z) of DSSCs based on these dyes are in the range of 2.1 to 4.2% and highly depend on their donor moiety. The incorporation of trans-10,20-dimesityl groups is highly beneficial for preventing the p-p aggregation among the porphyrin moieties, thus favorably suppressing the charge recombination and intermolecular interaction. Among all, pyrenyl appended Zn(II) porphyrin has exhibited a higher power conversion efficiency of 4.2% under 1 sun illumination due to the extended p-conjugation and electron donating ability of the pyrenyl moiety.